Analisis Meta: Determinan Minat Muzakki Membayar Zakat ke Organisasi Pengelola Zakat - Windi Wulandari Fitriani; Noven Suprayogi (Faculty of Economics and Management, 2023)
This study aims to determine the factors that influence the interest of muzakki to pay zakat in the Indonesian Zakat Management Organization (Organisasi Pengelola Zakat (OPZ)). This study uses a meta-analysis research method with quantitative approach. In this study, the dependent variable is interest in paying zakat in OPZ, and the independent variables are income, religiosity, and knowledge of zakat, transparency, service quality, and trust in muzakki. This study will re test the independent variables robustly to prove whether there is an effect of the independent variable on the dependent variable. The population in this study took research journal articles published in Google Scholar. The samples in this study are journal articles indexed by SINTA 1 to 6. This study accumulates and integrates existing studies using the meta-analysis technique developed by Hunter et al. (1982) on 22 sample articles. The results of testing the variables of income, religiosity, and knowledge of zakat, transparency, and trust in muzakki prove that there is a significant consistency of test results on the variable of muzakki's interest in paying zakat. While the calculation of the service quality variable states that it has no significant effect on the dependent variable.